Testing successful Business Model using System Dynamics - J. Ganzarain; M. Ruiz; J.I. Igartua (International Journal of Production Management and Engineering)
In our increasingly globalised economy, managing continuous change whilst remaining competitive and dynamic has become a central issue for firms in the industrial sector. One of the elements for obtaining this competitiveness is the value creation model of the firm. The most important challenges in firms are characterised by dynamic complexity which makes it difficult to understand factors in their context. Consequently management and decision making is hindered (Antunes et al., 2011). Business models are characterised by complexity and dynamism. Performance of the firm is a complex topic determined by the large amount of variables that can be involved in the system, and the different effects that influence the system in the short and long term. Due to this complexity a systemic view is required, that is, an holistic view of the whole system. Such a systemic view enables managers to make decisions based on evidence rather than intuition and personal experiences, as they understand how the whole system works. Thus, the main aim of this research is to use an empirical tool such as System Dynamics (SD), to support and sustain firms in the identification of new constructs related to their Business Model (BM).